Analisis Break Event Point Sebagai Alat Untuk Menentukan Komposisi Penjualan Dalam Pencapaian Target Laba (Studi Kasus pada CV. Sinar Logam di Natar Lampung Selatan) - M. Yusuf Sulfarano Barusman; . Farlina; Evi Ekawati (Universitas Bandar Lampung (UBL), 2010)
The research aims to determine the role of Break Even Point Analysis in determining the composition of sales in the achievement of profit targets of various products produced and sold by CV. Metal beams. While the usefulness of the research is to contribute ideas to the company in determining the composition of sales, while deepening science writers get obtained by comparing theory with the practice of the company. Of the above problems, the hypothesis: